Induced Orientation in Recrystallization of Polyacrylonitrile Precursor for Carbon Fiber in Steady-State High Magnetic Field - Xiao-Meng, Ren; Yuan-Sheng, Wang; Yong-Jia, Mei; Zheng-Cai, Xia; Te, He (Asian Journal of Chemistry, 2012)
Orientation of polyacrylonitrile precursor for carbon fiber was a critical factor to determine the performance of subsequent carbon fiber. In the study, polyacrylonitrile precursor was processed in a steady-state high magnetic field generated by PPMS. The magnetic field intensity was set in 8 T, 12 T, 16 T and the processing time was set for 10 min, 30 min, 50 min, respectively. The results showed that polyacrylonitrile precursor could be induced oriented in recrystallization and both crystalline and overall orientation increased when polyacrylonitrile precursor was processed in magnetic field. The mechanism of crystalline orientation was analyzed from magnetostatic energy, Boltzmann factor and moment of force points of view respectively and the three theories happened to coincide with each other. Moreover, polyacrylonitrile precursor was testified to be diamagnetic anisotropy. It was interesting to detect that the amorphous region was more susceptible to high magnetic field than crystallinity. The increase of overall orientation resulted from amorphous region mainly. The change of orientation brought about the changes of other properties which were measured by density, DSC, SEM.